An overview of the Nordic Battery Belt : an emerging network for cooperation within the Nordic battery cluster - Okonkwo, Ejike (Geographical society of Finland, 2022)
There is an increasing global demand for batteries in the decarbonisation process and an attempt to increase its production within Europe, thereby reducing the dependency on the Asian market. Consequently, the battery industry cluster is emerging in the Nordic region with the requisite raw materials for battery production in Norway, Sweden, and Finland. The industry will encounter medium- and long-term challenges in its supply value chain due to the envisaged transport connectivity issues in the region, especially as the industry begins experiencing growth. Regional networks will play a key role in mitigating these challenges by providing a space for cooperation among actors; however, how regional networks address these transport connectivity issues still needs to be explored. This paper introduces results from a qualitative study that adopts the network approach in examining the nature and the role of a novel network within the Nordic battery cluster. They show that the Nordic Battery Belt (NBB) is an emerging cross-border regional network established to proactively identify the prevailing and the envisaged connectivity challenges within the Nordic region. The NBB, therefore, contributes to the development of logistical strategies and inventories for sustainable and cost-effective transport systems, which will support the battery industry’s supply chain and reduce the industry’s carbon footprints. Overall, the paper advances the understanding of networks and their role in the regional energy transitions literature viz-a-viz the battery industry.
Keywords: battery industry; Cooperation; network; Nordic Battery Belt (NBB); regional energy transitions; fi=Aluetiede|en=Regional Studies|